2010
DOI: 10.1080/09243453.2010.500097
|View full text |Cite
|
Sign up to set email alerts
|

Examining relationships among elementary schools' contexts, leadership, instructional practices, and added-year outcomes: a regression discontinuity approach

Abstract: This study proposes and tests a multilevel structural model of school context, composition, and school leadership on school instructional practices and outcomes in elementary schools in a western state in the United States. We focus on direct and indirect relationships implied in our proposed model using an ''added year of schooling'' in reading and math as our primary school-level outcomes. Added-year effects, which result from a regression discontinuity design, represent a relatively new approach for describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 83 publications
3
37
0
3
Order By: Relevance
“…A major exception to the lack of specification in instructional leadership models is the model developed by Hallinger and his colleagues, along with the instrument the Principal Instructional Management Rating Scale (PIMRS), used to measure the enactment of this model (see, e.g., Hallinger & Heck, 1996;Hallinger & Murphy, 1985;Heck & Hallinger, 1999;Heck, Larsen, & Marcoulides, 1990;Heck & Moriyama, 2010;Leithwood & Montgomery, 1982). Defining the school mission is one of the three dimensions of this model of leadership (managing the instructional program and promoting a positive school culture aimed at improvement of teaching and learning being the other two dimensions).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…A major exception to the lack of specification in instructional leadership models is the model developed by Hallinger and his colleagues, along with the instrument the Principal Instructional Management Rating Scale (PIMRS), used to measure the enactment of this model (see, e.g., Hallinger & Heck, 1996;Hallinger & Murphy, 1985;Heck & Hallinger, 1999;Heck, Larsen, & Marcoulides, 1990;Heck & Moriyama, 2010;Leithwood & Montgomery, 1982). Defining the school mission is one of the three dimensions of this model of leadership (managing the instructional program and promoting a positive school culture aimed at improvement of teaching and learning being the other two dimensions).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Some of these studies highlighted the implementation of leadership in schools, collaboration, or the creation of a climate of trust [10][11][12][13][14][15][16][17]. Other have carried out specific training programs to improve teaching [18][19][20][21][22]. Some have focused on the analysis of the figure of teachers based on educational policies and reforms promoted by the state [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing concern about the need to become more involved staff were observed to achieve initiatives for internal change and strengthen distributed and pedagogical leadership in educational institutions. Related to that, Heck and Moriyama [22], based on a structural and multilevel model in primary schools, examined the impact of leadership on teaching practices and, therefore, on students' school results. Similar to Opdenakker and Van Damme [17], they found that contextual characteristics influence school outcomes, especially when there is room for a collaborative working context.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting examples are provided in indirect effect models of school leadership, where instructional conditions gradually become better integrated as important intermediary factors (cf. Heck & Moriyama, 2010;Scheerens, 2012).…”
Section: School Effectiveness and School Improvement 287mentioning
confidence: 99%